2015
DOI: 10.1387/ijdb.150136pr
|View full text |Cite
|
Sign up to set email alerts
|

CILP1 is dynamically expressed in the developing musculoskeletal system of the trout

Abstract: An in situ screen for genes expressed in the skeletal muscle of eyed-stage trout embryos led to the identification of a transcript encoding a polypeptide related to CILP1, a secreted glycoprotein present in the extracellular matrix. In situ hybridisation in developing trout embryos revealed that CILP1 expression was initially detected in fast muscle progenitors of the early somite. Later, CILP1 expression was down-regulated medio-laterally in differentiating fast muscle cells, to become finally restricted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Second, we found that embryonic MPCs in the dermomyotome express a number of ECM genes, including col1a2, col5a1 and cilp. Similarly, col1a1 and cilp are expressed in what is described as a dermomyotome-like domain in trout embryos (Ralliere et al, 2015;Rescan et al, 2005). Moreover, we found that the expression of these ECM genes is dynamically induced during muscle regeneration.…”
Section: Unique Features Of Col1a2 + Mpcssupporting
confidence: 56%
“…Second, we found that embryonic MPCs in the dermomyotome express a number of ECM genes, including col1a2, col5a1 and cilp. Similarly, col1a1 and cilp are expressed in what is described as a dermomyotome-like domain in trout embryos (Ralliere et al, 2015;Rescan et al, 2005). Moreover, we found that the expression of these ECM genes is dynamically induced during muscle regeneration.…”
Section: Unique Features Of Col1a2 + Mpcssupporting
confidence: 56%
“…We and others have previously shown that tenocytes are located along the myotendinous junction (MTJ), extending long cellular processes into the intersomitic space (Fig 2A) (Ma et al, 2018; Subramanian et al, 2018). Marker analysis revealed that nkx3.1 NTR-mCherry -positive cells along the MTJ were specifically labeled by known tendon markers such as scxa, cilp , and tnmd (Chen and Galloway, 2014; Ralliere et al, 2015) (Fig 2C). By contrast, interstitial fibroblasts were scattered throughout the interstitial space and displayed varied morphologies (Fig 1C and 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Myoseptal cells become apparent between adjacent myomeres only after the completion of somitogenesis (Bricard et al, 2014;Charvet et al, 2011;Chen & Galloway, 2014). These myoseptal cells that express scleraxis and tendon associated collagens are considered homologous to axial tenocytes in amniotes (Bricard et al, 2014;Chen & Galloway, 2014;Ralliere et al, 2015;Subramanian & Schilling, 2014). Similar to the axial tenocytes in amniotes (Brent et al, 2003), myoseptal cells are likely to originate from a syndetome compartment that derives from a subdomain of the early fish sclerotome.…”
Section: Introductionmentioning
confidence: 99%